The role of higher aquatic plants in the degradation of pollutants in bioengineered hydrophilic facilities - Маджд C. М.; Панченко, А. О.; Бондар, А. М. (Science-based technologies, 2017)
The article includes information concerning analysis of higher aquatic plants which are used in hydrophilic systems of waste water treatment. It was analyzed the ability of macrophytes to treat waste water from different pollutants. It was defined how different plant groups influenced on appropriate pollutants. In the article are showed several examples of different macrophytes using in bioengineered hydrophilic facilities. It was analyzed its effectiveness during waste water treatment created by different enterprises. It was conducted its treatment capacity of dangerous and toxic substances. It was proven benefits of higher aquatic plants using in order of water polluted by surfactants and oil products treatment. It was described the influence of different pollutant on specific macrophytes and their their treatment ability by this pollutants.